1992
DOI: 10.1523/jneurosci.12-02-00376.1992
|View full text |Cite
|
Sign up to set email alerts
|

beta-Amyloid peptides destabilize calcium homeostasis and render human cortical neurons vulnerable to excitotoxicity

Abstract: In Alzheimer's disease (AD), abnormal accumulations of beta-amyloid are present in the brain and degenerating neurons exhibit cytoskeletal aberrations (neurofibrillary tangles). Roles for beta-amyloid in the neuronal degeneration of AD have been suggested based on recent data obtained in rodent studies demonstrating neurotoxic actions of beta-amyloid. However, the cellular mechanism of action of beta-amyloid is unknown, and there is no direct information concerning the biological activity of beta-amyloid in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
926
2
12

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,550 publications
(978 citation statements)
references
References 51 publications
(84 reference statements)
38
926
2
12
Order By: Relevance
“…Recent findings indicate that a primary target of ␤-amyloid peptide is SDH (Kaneko et al, 1995) and that ␤-amyloid peptide results in the loss of energy homeostasis (Zhang et al, 1996). Moreover, ␤-amyloid can induce apoptotic neuronal death (Loo et al, 1993) and exacerbate glutamate toxicity (Koh et al, 1990;Mattson et al, 1992). The 3-NP model established in the current study is therefore relevant to acute insults such as ischemia, as well as neurodegenerative disorders, including Huntington's disease and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 94%
“…Recent findings indicate that a primary target of ␤-amyloid peptide is SDH (Kaneko et al, 1995) and that ␤-amyloid peptide results in the loss of energy homeostasis (Zhang et al, 1996). Moreover, ␤-amyloid can induce apoptotic neuronal death (Loo et al, 1993) and exacerbate glutamate toxicity (Koh et al, 1990;Mattson et al, 1992). The 3-NP model established in the current study is therefore relevant to acute insults such as ischemia, as well as neurodegenerative disorders, including Huntington's disease and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 94%
“…47 Briefly, meninges-free cortices were isolated, trypsinized and mechanically dissociated by passage through fire-polished Pasteur pipettes. Washed cells were plated (200 000 cells cm À2 ) onto poly-L-lysine (0.05 mg ml À1 ) and laminin (0.1 mg ml À1 )-coated tissue culture coverslips (Fisher Brand; Fisher Scientific, Pittsburgh, PA, USA) in NBM with L-glutamine, B-27 and P/S supplements (complete NBM).…”
Section: Primary Cortical Neuron Culturesmentioning
confidence: 99%
“…In the hippoca mpus amyloid protein precursor, a single pass transmembrane protein, is cleaved by secretases into Aβ40 and Aβ42. Increases in the secretion and aggregation of Aβ molecules are thought to be responsible for cell toxicity and memory impairment in AD (Koh et al, 1990;Yankner et al, 1990;Mattson et al, 1992Mattson et al, , 1993Morgan et al, 2000;Naslund et al, 2000). A series of studies have shown that levels of soluble Aβ correlate with the degree of cognitive impairment and disease progression in animal models and AD subjects (Kuo et al, 1996;McLean et al, 1999;Mucke et al, 2000;Naslund et al, 2000) whereas increasing evidence has suggested that soluble non-fibrillar Aβ rather than the insoluble fibrillar counterpart is important for the pathophysiology of the disease (Walsh 1999;Lambert et al, 2000).…”
Section: Introductionmentioning
confidence: 99%